Predicting Satisfaction with Group Work Assignments - Burdett, Jane; Hastie, Brianne (Journal of University Teaching and Learning Practice, 2009)
Universities are increasingly using group based assessment tasks; however, as with workplace teams, such tasks often elicit mixed feelings from participants. This study investigated factors that may predict student satisfaction with group work at university. Final-year business students completed a questionnaire addressing experiences of group work. Quantitative and qualitative data suggest that the major barrier to students’ group work satisfaction was workload issues. Conversely, perceptions of learning and feelings of group-based achievement contributed most to satisfaction. Knowledge of predictors of satisfaction allows teaching staff to identify potential problems in groups, and improve the quality of the group work experience.